KAUSALITAS PENERIMAAN, BELANJA DAN PDRB PROVINSI JAMBI - Fitrina Afrianti (Jurnal Ekonomi Sakti, 2020)
This study aims to determine the causality between regional revenue and regional expenditure in Jambi Province, to determine the causality between regional revenue and GRDP in Jambi Province, and to determine the causality between regional spending and GRDP in Jambi Province. The result of the research that has been done is that there is a causality (two ways) between regional revenue and expenditure. This means that the higher regional expenditure, it can trigger an increase in regional revenue in Jambi Province, on the other hand, the higher the regional revenue, the higher regional spending in Jambi Province. Meanwhile, regional revenues and PDRB do not have a two-way causality relationship. This means that regional revenues have a relationship with GRDP, but on the other hand, PDRB has no relationship with regional revenues. Regional spending and GRDP do not have a two-way causal relationship. Regional spending has a relationship with GRDP, but on the other hand, GRDP has no relationship with regional spending.